Pengaruh Literasi Keuangan dan Teman Sebaya Terhadap Perilaku Keuangan dengan Gaya Hidup Sebagai Variabel Mediasi Pada Mahasiswa Institut Bisnis dan Ekonomi Indonesia - Ecci Resamala Sari; Yusron Toto; Yuniarti Yuniarti; Sukma Febrianti (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This research aims to analyze and determine the influence of financial literacy and peers on financial behavior with lifestyle as a mediating variable (Study of students at the Indonesian Institute of Business and Economics). The population of this study was 821 IBE Indonesia students class 2021- 2024, the sampling technique used purposive sampling and the sample formula was Taro Yamane with an error rate of 5%, a sample of 268 respondents was obtained. The data collection technique uses a questionnaire from Google Form and the data analysis tool uses Smart PLS 4.0. The data analysis technique uses PLS-SEM. Based on the results of this research, it can be concluded that financial literacy has a positive influence on financial behavior. Apart from that, the existence of peer variables also has a significant positive impact on financial behavior. Financial literacy and peers also contribute positively and significantly to lifestyle. Finally, lifestyle plays a role in mediating the relationship between financial literacy and financial behavior, as well as between peers and financial behavior.